2018
DOI: 10.4314/jfas.v9i6s.88
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity for measurement of body composition: A field method

Abstract: Measurement of body composition via a field method has the most popular instruments which are used to estimate the percentage of body fat. Among the instruments used are the Body Mass Index, Bio Impedance Analysis and Skinfold Test. All three of these instruments do not involve high costs, do not require high technical skills, mobile, save time, and are suitable for use in large populations. Because all three instruments can estimate the percentage of body fat, but it is important to identify the most appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The reliability of the body composition measurement by bioelectric impedance method has been reported. Hashim et al (2017) reported that the test-retest reliability and interclass reliability were high (r= 0.99 and 0.96 respectively) [15]. Furthermore, an intraclass reliability coefficient of 0.97 was reported [15].…”
Section: Instruments/materialsmentioning
confidence: 99%
“…The reliability of the body composition measurement by bioelectric impedance method has been reported. Hashim et al (2017) reported that the test-retest reliability and interclass reliability were high (r= 0.99 and 0.96 respectively) [15]. Furthermore, an intraclass reliability coefficient of 0.97 was reported [15].…”
Section: Instruments/materialsmentioning
confidence: 99%